Probing the geometry of copper and silver adatoms on magnetite: quantitative experiment versus theory. Issue 5 (15th January 2018) - Meier, Matthias; Jakub, Zdeněk; Balajka, Jan; Hulva, Jan; Bliem, Roland; Thakur, Pardeep K.; Lee, Tien-Lin; Franchini, Cesare; Schmid, Michael; Diebold, Ulrike; Allegretti, Francesco; Duncan, David A.; et al.
Abstract : Benchmarking DFT calculations against precise normal incidence X-ray standing wave measurements. Abstract : Accurately modelling the structure of a catalyst is a fundamental prerequisite for correctly predicting reaction pathways, but a lack of clear experimental benchmarks makes it difficult to determine the optimal theoretical approach. Here, we utilize the normal incidence X-ray standing wave (NIXSW) technique to precisely determine the three dimensional geometry of Ag1 and Cu1 adatoms on Fe3 O4 (001). Both adatoms occupy bulk-continuation cation sites, but with a markedly different height above the surface (0.43 ± 0.03 Å (Cu1 ) and 0.96 ± 0.03 Å (Ag1 )). HSE-based calculations accurately predict the experimental geometry, but the more common PBE + U and PBEsol + U approaches perform poorly.